Strategi UI/UX Dalam Meningkatkan Engagement Pada Aplikasi Toko Online Galery Parfum Dengan Metode User-Centered Design (UCD) - Gynandra Alexsander Ginting; Sri Wahyuni; Hermansyah (CV. Hawari, 2026)
The rapid growth of e-commerce requires online shopping applications to focus not only on transactional functionality but also on the quality of User Interface (UI) and User Experience (UX) in order to enhance user engagement. This study aims to design and evaluate UI/UX strategies for the Galery Parfum online store application through the implementation of the User-Centered Design (UCD) method. This method was selected because it places users at the core of each design stage, enabling the development of solutions that are more aligned with users’ needs and characteristics. The research was conducted through four UCD stages: Understand Context of Use, Specify User Requirements, Design Solutions, and Evaluate Against Requirements. Data were collected through observations, questionnaires, and prototype usability testing involving users. The results indicate that users require a simple interface, intuitive navigation, and informative fragrance descriptions to support online purchase decision-making. The application prototype was developed using Figma, incorporating clear user flows for both customers and administrators. Usability evaluation using the System Usability Scale (SUS) yielded an average score of 77.75, which falls into the Good category with an acceptable level of acceptability. These findings demonstrate that the UI/UX design of the Galery Parfum application has good usability and contributes to improving user experience and engagement. This study is expected to serve as a reference for the development of UI/UX in e-commerce applications, particularly for experience-based products such as perfumes.